Rodent Models of Nonalcoholic Fatty Liver Disease/Nonalcoholic Steatohepatitis - Imajo, Kento (Molecular Diversity Preservation International (MDPI), 2013)
Research in nonalcoholic fatty liver disease (NAFLD), including nonalcoholic steatohepatitis (NASH), has been limited by the availability of suitable models for this disease. A number of rodent models have been described in which the relevant liver pathology develops in an appropriate metabolic context. These models are promising tools for researchers investigating one of the key issues of NASH: not so much why steatosis occurs, but what causes the transition from simple steatosis to the inflammatory, progressive fibrosing condition of steatohepatitis. The different rodent models can be classified into two large groups. The first includes models in which the disease is acquired after dietary or pharmacological manipulation, and the second, genetically modified models in which liver disease develops spontaneously. To date, no single rodent model has encompassed the full spectrum of human disease progression, but individual models can imitate particular characteristics of human disease. Therefore, it is important that researchers choose the appropriate rodent models. The purpose of the present review is to discuss the metabolic abnormalities present in the currently available rodent models of NAFLD, summarizing the strengths and weaknesses of the established models and the key findings that have furthered our understanding of the disease’s pathogenesis.